Deendayal Upadhyaya’s Integral Humanism and the Indian Knowledge System: A Philosophical Synthesis - Sharma, Sapna Kumari (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
This paper explores the deep conceptual connections between the Indian Knowledge System (IKS), the Advaitic ontology of non-dualism and the Integral Humanism of Deendayal Upadhyaya or Ekatma Manav Darshan. The Indian philosophical tradition introduces reality as a unified entity, which is interdependent and intrinsically unified, which can be also seen in Vedanta, Sāṃkhya or the Purusharthas system. Upadhyaya takes this metaphysics into a socio-political paradigm which focuses on the organic unity of individuals, society, nature and the cosmos. His holism in the holistic development is based on the spiritual and ethical precepts and this can be seen as a reaction to the materialist ideologies of the West. Through a methodological analysis of the main ideas of non-dualistic ontology, integral anthropology, and the dharmic approach to the organization of society, the paper shows that Integral Humanism reflects and replicates the insights of the Indian Knowledge System to the modern system of governance and human development.